PENGARUH PENERAPAN BONUS PADA TABUNGAN WADI'AH (YAD DHAMANAH) DAN NISBAH BAGI HASIL TABUNGAN MUDHARABAH TERHADAP TINGKAT KEPUASAN NASABAH (STUDI KASUS BSI KCP MEDAN PULO BRAYAN) - Ifti Ayuni; Ahmad Perdana Indra; Tuti Anggraini (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to ascertain the connection between and consequences of the installation of bonuses on savings wadi'ah (yad dhamanah) and the ratio of savings income to customer satisfaction. This sort of analysis is quantitative and uses data from the whole customer base of the bank BSI KCP Medan Pulo Brayan in 2022. Of those customers, 3.210 used the savings yad adh-dhamanah product and 5.540 used the savings mudharabah product. According to the study's findings, customer satisfaction in Bsi Kcp Campo Pulo Brayan was greatly positively impacted by partially displaying the Wadi'ah Savings Bonus and the ratio of income from savings. Ratio to Results (X2) has a strong beneficial effect on customer satisfaction in Bsi Kcp Field Pulo Brayan while also displaying Wadi'ah Savings Bonus (X1). It has been established that this has a Fitung value of 552,773 and a significance of 0. For the value of Calculus > Ftable is 552,773 > 3.09, and at the significance value () 0.05 is 0,000 0.05. As a result, it can be said that Wadi'ah Savings Bonus (X1) and Ratio to Mudharabah Savings Outcome (X2), two free factors, simultaneously have a considerable beneficial influence on bound variables related to customer happiness. (Y). Keywords : Wadi’ah Savings Bonus, Proportion to Results, Savings in Expenses, Customer Satisfaction